Investigation Of Hydraulic Performance On Unsymmetrical Smooth Spillway - Saidin, Mohd Safarul Izmi (2021)
The smooth spillway is a classic design used to spill large volume of water from the dam reservoir. Several studies of hydraulic characteristics of the spillway have been conducted experimentally and numerically in recent decades to provide a better insight into flow behaviour and predict any critical area that could endanger the structure and environment. An experimental study was carried out on a laboratory scale model to investigate basic hydraulic characteristics of the unsymmetrical smooth spillway with three sizes of discharge namely as Q1, Q2 and Q3. Next, the simulation verification were done using grid independent test (GIT), time step size analysis, and simulation time observation. In simulation, Reynolds-averaged Navier-Stokes (RANS) equation, volume of fluid (VOF) scheme and Standard κ-ω (SKW) turbulence model with appropriate boundary conditions were used to simulate the unsymmetrical smooth spillway geometry with four sizes of discharge namely as Q1, Q2, Q3 and Q4. The simulation results provide a good prediction of the hydraulic characteristics of water flow on the unsymmetrical smooth spillway and show a good agreement in terms of water surface and velocity profiles patterns with the experimental results. In the last objective, four chute piers modification models (diverge -45 degree, diverge -15 degree, converge 15 degree and converge 45 degree) were simulated using Q3 and Q4 discharge water flows and the hydraulic jump performance of all models were compared with the normal geometry. For all modification models, the converge 15 degree model showed 5.06% and 2.49% higher energy dissipation than the normal geometry model using Q3 and Q4, respectively. The chute piers modifications on unsymmetrical spillway will affect the energy dissipation performance at stilling basin and provide good insight which can be considered for spillway design in the future.